2014
DOI: 10.19173/irrodl.v15i3.1680
|View full text |Cite
|
Sign up to set email alerts
|

Peer assessment for massive open online courses (MOOCs)

Abstract: The teach-learn-assess cycle in education is broken in a typical massive open online course (MOOC). Without formative assessment and feedback, MOOCs amount to information dump or broadcasting shows, not educational experiences. A number of remedies have been attempted to bring formative assessment back into MOOCs, each with its own limits and problems. The most widely applicable approach for all MOOCs to date is to use peer assessment to provide the necessary feedback. However, unmoderated peer assessment resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 16 publications
0
88
0
Order By: Relevance
“…With the massive number of participants in a course, conducting assessments by the instructors is impossible (Glance et al, 2013;Sandeen, 2013;Suen, 2014) and different models of assessments are evolving, including: automated quizzes, peer assessments, and self-assessments. Nevertheless, studies indicated that with free and easy registration for MOOCs, the courses include a large number of participants who may not have any interest in completing the assessments (Breslow et al, 2013;Ho et al, 2014).…”
Section: Background Moocs Learning Resourcesmentioning
confidence: 99%
“…With the massive number of participants in a course, conducting assessments by the instructors is impossible (Glance et al, 2013;Sandeen, 2013;Suen, 2014) and different models of assessments are evolving, including: automated quizzes, peer assessments, and self-assessments. Nevertheless, studies indicated that with free and easy registration for MOOCs, the courses include a large number of participants who may not have any interest in completing the assessments (Breslow et al, 2013;Ho et al, 2014).…”
Section: Background Moocs Learning Resourcesmentioning
confidence: 99%
“…The value of using rubrics to support peer feedback has been shown previously (cf. Suen 2014). Also in our case, a combination of multiple criteria or rubrics along with significantly weighting the feedback were demonstrated to help circumvent this frustration.…”
Section: Discussionmentioning
confidence: 78%
“…From a Constructivist perspective, when designing a MOOC it is recommended to include peer-to-peer assessment strategies in order to encourage learning, collaboration and participation in the community (Suen, 2014). At the end of each test or activity, opening a discussion group about that task in particular allows participants to share similar difficulties.…”
Section: Contributions Of the Learning Theories On Which The Instructmentioning
confidence: 99%
“…1 simple and easy to understand for students 2 efficient in execution without occupying much time 3 limited in that each student rater is asked to rate no more than a handful of other students' assignments (Suen, 2014).…”
Section: Feedback and Certificationmentioning
confidence: 99%